2014
DOI: 10.1038/srep04976
|View full text |Cite
|
Sign up to set email alerts
|

Engineering surface states of carbon dots to achieve controllable luminescence for solid-luminescent composites and sensitive Be2+ detection

Abstract: Luminescent carbon dots (L-CDs) with high quantum yield value (44.7%) and controllable emission wavelengths were prepared via a facile hydrothermal method. Importantly, the surface states of the materials could be engineered so that their photoluminescence was either excitation-dependent or distinctly independent. This was achieved by changing the density of amino-groups on the L-CD surface. The above materials were successfully used to prepare multicolor L-CDs/polymer composites, which exhibited blue, green, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
456
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 615 publications
(491 citation statements)
references
References 60 publications
34
456
0
1
Order By: Relevance
“…[34][35][36][37] However, up to now, no research on surface chemical states can be found for IPQDs. Figure 7 presents the X-ray photoelectron spectroscopy (XPS) results of CsPbBr 3 CPB-M and CPB-C QDs.…”
Section: Surface Self-passivation and Cspbx 3 @X Quantum-well Band Almentioning
confidence: 98%
“…[34][35][36][37] However, up to now, no research on surface chemical states can be found for IPQDs. Figure 7 presents the X-ray photoelectron spectroscopy (XPS) results of CsPbBr 3 CPB-M and CPB-C QDs.…”
Section: Surface Self-passivation and Cspbx 3 @X Quantum-well Band Almentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8] Especially, CDs, owing to their superior performance in terms of water solubility, stability, toxicity, resistance to photobleaching, and biocompatibility, have recently drawn significant attention. [9][10][11][12][13][14][15] The electron injection from CDs to TiO 2 was demonstrated to be feasible and the CD-sensitized TiO 2 photoelectrodes have been applied in photocatalysis and PVs. 10,[16][17][18][19][20][21] However, it is still a challenge to achieve efficient electron injection from CDs to TiO 2 under sunlight, 21 which is a primary photophysical process in generating photocurrent in CD-based PVs.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 The existence of many hydroxyl and/or carboxyl moieties on their surface facilitates their surface functionalization with various organic, polymeric, inorganic, or biological species. 32,33 This could inuence their uorescence properties.…”
Section: -29mentioning
confidence: 99%